Review of Processing Maps and Development of Qualitative Processing Maps. (2017) - Anitha Lakshmi, A.; Srinivasa Rao, Ch.; Gangadhar, J.; Srinivasu, Ch.; Singh, Swadesh Kumar
Abstract: Significant investigations in the area of theory of processing maps for hot working of different materials are reviewed. Special attention is focused on Dynamic Material Model, Power Dissipation Maps, Instability Maps, Hot Deformation Mechanisms, which are generally believed to be the dominant factors for determining processing maps at different temperatures and strain rates. The basic constitutive equation describing the process in which power is converted at any instant into different forms is presented along with a general survey of the numerous papers, investigating specific linear and nonlinear effects on these models. Estimates of the associated temperature ranges and strain rates are discussed, and a summary of relevant experimental results is given. Studies of the Hot Deformation Mechanisms like Dynamic Recrystallization (DRX), Super plastic Deformation, Dynamic recovery (DRY) are also surveyed. Methodology for development of qualitative processing maps for warm forming of different materials is discussed.